Public perception of "scarless" surgery: a critical analysis of the literature - Autorino, R (2013)
Evidence relating to the perception and view of patients and physicians on natural orifice transluminal endoscopic surgery (NOTES) and laparoendoscopic single-site surgery (LESS) was scrutinized. A comprehensive literature search was performed through PubMed. A total of 18 studies were included in the analysis. Patients demonstrated interest in scarless surgery, with a preference for LESS over NOTES. Safety and efficacy remain the key factors in the decision-making process of patients. With more information about the safety and reproducibility of LESS and NOTES, and with improved educational efforts, patients and physicians alike may feel more comfortable in widespread application of scarless surgery.